Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð½Ð¸Ð·ÐºÐ¾Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð½Ð¾Ð³Ð¾ Ñ…Ñ€Ð°Ð½ÐµÐ½Ð¸Ñ Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð½Ð° Ñ„Ð°Ð·Ð¾Ð²Ñ‹Ðµ Ð¿ÐµÑ€ÐµÑ…Ð¾Ð´Ñ‹ Ð²Ð¾ Ñ„Ñ€Ð°ÐºÑ†Ð¸ÑÑ… ÑÐºÑÑ‚Ñ€Ð°ÐºÑ‚Ð¾Ð² Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ Ð¸ Ð² ÑÐ¼ÐµÑÑÑ… Ñ„Ñ€Ð°ÐºÑ†Ð¸Ð¹ Ñ ÐºÐ»ÐµÑ‚ÐºÐ°Ð¼Ð¸ - Zinchenko, Aleksandra V.; Bobrova, Elena N.; Govorova, Yulianna S.; Rozanova, Ekaterina D.; Karpenko, Vladimir G. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2015)
There were studied the phase transitions in fractions of extracts from human placenta, stored at –20 and –196°C as well as the mixtures of erythrocyte and Sacchamyces cerevisiae suspensions with fractions at the temperatures below 0°C. Fractions with molecular weight below 4, 50–60 and above 150 kDa were obtained by gel chromatography. Phase transitions were recor-ded by low temperature differential scanning calorimetry. It was shown that temperatures of phase transitions and character of their manifestation in fractions of placental extracts did not change during their storage for 6 months both at –20 and –196°C. The changes of molecule-to-molecule interactions in environment of extract fractions supplemented with cell suspensions result in the increase of inversion temperature by 4–9 degrees and reduction of eutectics melting temperature by 4–6 degrees, as well as to a significant decrease of intensity of their peaks. Moreover, melting temperatures of entire system remained unchanged within the ranges of the experimental error. There was also found the reduction of inversion peaks intensity in 2–5 times and eutectic melting peak in 7–15 times in mixtures of the fractions and cell suspensions, depending on the cell type and conditions of placenta storage. It has been shown that placenta low-temperature storage did not affect the phase transition temperatures in the mixtures, containing suspensions of erythrocytes or S. cerevisiae and the fractions of extracts derived from this placenta. Probl Cryobiol Cryomed 2015; 25(2): 122-130